The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1308/rcsann.2016.0057
|View full text |Cite
|
Sign up to set email alerts
|

Surgical outcome and patterns of recurrence for retroperitoneal sarcoma at a single centre

Abstract: Retroperitoneal sarcoma is commonly an infiltrative tumour and often recurs outside of the retroperitoneum. These features limit the therapeutic impact of interventions that focus on gaining local control such as complete compartmental resection and radiotherapy. It seems likely that future advances in the management of this cancer will involve new systemic agents to treat this frequently systemic disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 14 publications
(23 reference statements)
0
7
0
Order By: Relevance
“…This remains technically difficult because of deep-seated location, multifocality, and necessity of multi-visceral resections [4]. The principal cause of failure is locally recurrent disease, [5] with debate concerning the value of adjuvant chemotherapy and/or radiotherapy [6]. Risk stratification is based upon the American Joint Committee on Cancer (AJCC) staging for soft tissue sarcomas (STS) of the extremity, where the main factors implicated in survival include the histologic tumor grade, the pathologic subtype, and the resection margins [7].…”
Section: Introductionmentioning
confidence: 99%
“…This remains technically difficult because of deep-seated location, multifocality, and necessity of multi-visceral resections [4]. The principal cause of failure is locally recurrent disease, [5] with debate concerning the value of adjuvant chemotherapy and/or radiotherapy [6]. Risk stratification is based upon the American Joint Committee on Cancer (AJCC) staging for soft tissue sarcomas (STS) of the extremity, where the main factors implicated in survival include the histologic tumor grade, the pathologic subtype, and the resection margins [7].…”
Section: Introductionmentioning
confidence: 99%
“…The other study, Hogg et. al, it was noti ed in 88.9% (80, total 90) [11]. Our nding that all patients had a macroscopically clear margin is thus superior to conventional studies.…”
Section: Discussionmentioning
confidence: 60%
“…The Memorial Sloan Kettering Cancer Center reported that majority of patients with RPS died of advanced local tumor recurrence in the absence of systemic diseases (9). A lot of effort to improve the OS of RPS was focused on local control through adjuvant radiotherapy or surgical techniques (10). Although adjuvant radiotherapy tended to be beneficial to improve OS (11), surgery remains the mainstay of curative therapy for RPS (12).…”
Section: Discussionmentioning
confidence: 99%